Where not to fish – reviewing and mapping fisheries restricted areas in the Aegean Sea - PETZA, D.; MAINA, I.; KOUKOUROUVLI, N.; DIMARCHOPOULOU, D.; AKRIVOS, D.; KAVADAS, S.; TSIKLIRAS, A.C.; KARACHLE, P. K.; KATSANEVAKIS, S. (Mediterranean Marine Science, 2017)
An up-to-date systematic review and unofficial codification of the national fisheries legislation was performed, along with an up-to-date systematic review of environmental, archaeological and maritime legislation, about spatio-temporal restrictions of fishing activities by all fishing gears in the Aegean Sea. Spatio-temporal restrictions established by the European Union and the General Fisheries Commission for the Mediterranean were also reviewed. A database was built, including detailed information on the Fisheries Restricted Areas (FRAs) being identified. All FRAs were mapped, as polygons in Geographic Information System shapefiles. The national fisheries, environmental, archeological and maritime legal framework comprises of 32, 2, 37 and 43 legal acts respectively; EU and GFCM legislation consists of one Regulation and one Recommendation respectively. A total of 511 national (254 of fisheries, 21 of environmental, 85 of archaeological and 151 of the maritime legislation), 6 EU and 4 international FRAs were identified, out of which 85.2% are located in the Aegean Sea and 14.8% in Crete. Towed or mobile gears are restricted in 88.5% of the FRAs, while static gears are restricted in only 10.2% of FRAs. Fish stocks and Posidonia oceanica beds protection are the most common reasons for regulating fishing activities (25.3% and 25.0% respectively). Most of the FRAs (85.4%) impose permanent closures. National fisheries, environmental, archaeological, maritime, EU and international FRAs cover 25.8%, 1.0%, 1.1%, 0.4%, 13.5% and 22.6% of the study area, respectively. The present study provides valuable information for the Maritime Spatial Planning in the Aegean Sea.